1999
DOI: 10.1021/js980407q
|View full text |Cite
|
Sign up to set email alerts
|

Sites of elimination and pharmacokinetics of recombinant [131I]lepirudin in baboons

Abstract: Lepirudin has a short half-life, and only 50-60% of the intravenously administered dose is excreted by the kidneys. The fate of the remainder is unknown. We designed a study to determine the fate of this lepirudin. In each of six baboons, [131I]lepirudin was given intravenously as a bolus or infused over 30 min, 24 h apart. The in vivo redistribution of [131I]lepirudin was determined and quantified by scintillation camera imaging. In all studies, the half-life of [131I]lepirudin, as determined from the disappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This IgG activates platelets in the presence of pharmacologic concentrations of heparin 10–15 . The pharmacokinetics of hirudin in laboratory animals was found to be similar to humans 16–21 . The renal clearance of hirudin approximates the renal clearance of creatinine suggesting clearance by glomerular filtration.…”
mentioning
confidence: 93%
“…This IgG activates platelets in the presence of pharmacologic concentrations of heparin 10–15 . The pharmacokinetics of hirudin in laboratory animals was found to be similar to humans 16–21 . The renal clearance of hirudin approximates the renal clearance of creatinine suggesting clearance by glomerular filtration.…”
mentioning
confidence: 93%
“…Richter et al [9] reported the t 1/2β was 65 min for rats and 56.6 min for dog by using the 125 I-rH combined with thrombin titration assay. The t 1/2β of rH in baboons was determined as 24 min and 23 min by using the 131 I-labeled rH combined the ecarin Clotting Time (ECT) method by Meiring et al [13]. Recently, Huang et al [8] reported that in rats, the t 1/2β was 172.8 min by the total plasma 125 I-labeled rH radioactivity (RA) method and 107 min by the trichloroacetic acid precipitate plasma 125 I-labeled rH radioactive activity (TCA-RA) method.…”
Section: Introductionmentioning
confidence: 99%